Systematic review and classification of: The Learning Environment Project - Holen, Solveig Ingebjørg; Strøm, Henriette Kyrrestad (Ungsinn. Journal of Effective Interventions for Children and Adolescents, 2025)
Background: The Learning Environment Project is a preventive intervention designed for employees in schools and kindergartens where bullying is persistently prevalent. The Learning Environment Project aims to promote a safe and positive kindergarten and school environment free from dissatisfaction and violations such as bullying, violence, discrimination, and harassment. . Launched in 2013, this initiative has been developed and executed by the Norwegian Centre for Learning Environment and Behavioral Research in Education at the University of Stavanger in collaboration with The Norwegian Directorate for Education and Training. While the Norwegian Directorate for Education and Training owns the initiative, the responsibility for its implementation lies with the Norwegian Centre for Learning Environment. Method: This review is based on a systematic literature search in the databases Embase, Medline, Psykinfo, NORART, Cochrane, Cristin, NORA, SCOPUS and SweMed. International databases on evidence have also been searched, as well as information about the intervention from the program provider. Re-sults from literature searches and the other information obtained were reviewed to identify Nordic effect studies, international systematic reviews, and eventually other Norwegian studies of the in-tervention. Results: The Learning Environment Project is a versatile intervention strategy, primarily involving professional meetings and guidance facilitated by trained personnel. It encompasses well-defined implementation procedures as well. The specific content of the initiative is adaptable based on the primary challenges faced by the school and/or kindergarten in question. Although there are no Nordic effectiveness studies, other evaluations have been carried out. The overarching observation from these evaluations underscores that a significant number of participants have reported heightened proficiency in addressing and preventing bullying. Participants generally express contentment with the meetings and guidance provided, yet they highlight the need for greater involvement of PPT, teachers, parents and students. Conclusion: The Learning Environment Project is classified at evidence level 2 – Theoretically-based intervention.
Keywords: Learning Environment Project; School environment; Kindergarten environment; Bullying; Prevention; Classroom management